Micelles prepared from poly(N-isopropylacrylamide-co-tetraphenylethene acrylate)-b-poly[oligo(ethylene glycol) methacrylate] double hydrophilic block copolymer as hydrophilic drug carrier. Issue 45 (30th October 2018) - Xu, YangYang; Li, Gaocan; Zhuang, Weihua; Yu, HongChi; Hu, Yanfei; Wang, Yunbing
Abstract : Thermal-induced micelles prepared with P(NIPAAm- co -TPE)- b -POEGMA double hydrophilic block copolymers for hydrophilic drug release. Hydrogen bonds are formed between PNIPAAm and thymopentin. Abstract : Self-assembled micelles obtained from a double hydrophilic block copolymer (DHBC) based on poly( N -isopropylacrylamide) (PNIPAAm) are a facile and green strategy compared to the conventional solvent exchange method. However, hydrophobic drug encapsulation in micelles from PNIPAAm-based DHBC has relatively low drug loading (DL) and encapsulation efficiency (EE). Intermolecular and intramolecular hydrogen bondings of PNIPAAm chains are formed to exclude hydrophobic drugs. Nevertheless, hydrogen bonding can be used for hydrophilic drug delivery. Therefore, we report micelles prepared from a poly( N -isopropylacrylamide- co -tetraphenylethene acrylate)- b -poly[oligo(ethylene glycol) methacrylate] [P(NIPAAm- co -TPE)- b -POEGMA] double hydrophilic block copolymer as a hydrophilic drug (thymopentin, TP5) carrier. The FTIR results confirm hydrogen bond formation between PNIPAAm chain and TP5. Micelles are obtained by simply increasing the temperature above the critical micelle temperature (CMT). The self-assembly behaviour of polymeric micelles is investigated by DLS, TEM and aggregation-induced emission (AIE) phenomenon. Cytotoxicity results indicate that the micelles are biocompatible. The in vitro prolonged drug release (from 6 min to several hours) and in vivo immunity enhancement indicate that the micelles formed by P(NIPAAm- co -TPE)- b -POEGMA DHBC are promising candidates as hydrophilic drug carriers, where hydrogen bonding is formed between PNIPAAm and drug.